High‐Power Graphene–Carbon Nanotube Hybrid Supercapacitors. Issue 6 (18th May 2017) - Ansaldo, Alberto; Bondavalli, Paolo; Bellani, Sebastiano; Del Rio Castillo, Antonio Esau; Prato, Mirko; Pellegrini, Vittorio; Pognon, Grégory; Bonaccorso, Francesco
Abstract: The bulky structure of current power sources is hindering the widespread development of next‐generation electronics. Here, we propose a graphene/single wall carbon nanotube (SWCNT) hybrid structure for the realization of high‐performance supercapacitors. The devices are assembled by using 2 cm 2 area hybrid graphene/SWCNT electrodes, designed by combining a scalable solution‐processing method (e.g., liquid phase exfoliation of pristine graphite and de‐bundling of SWCNTs) with dynamic spray‐gun deposition, and an aqueous electrolyte (3 m LiNO3 ). This architecture allows us to effectively balance the supercapacitors performance achieving remarkable electrode gravimetric capacitance and specific energy at 2 mV s −1 of 104 F g −1, 20.8 Wh kg −1, respectively, and a maximum specific power of 92.3 kW kg −1 . Our results, based on industrially scalable materials production and deposition methods, represent a real breakthrough compared to state‐of‐the‐art lab‐scale devices. Abstract : Graphene/single wall carbon nanotube (SWCNT)‐based hybrid supercapacitors have been fabricated based on scalable solution‐processing methods. The gravimetric capacitance, specific energy and power of the resulting devices are 104 F g −1, 20.8 Wh kg −1, and 92.3 kW kg −1, respectively. These results represent a real breakthrough compared to state‐of‐the‐art lab‐scale devices.